PERISTILAHAN AKTIVITAS MENANGKAP IKAN DI ALIRAN SUNGAI LANDAK DALAM BAHASA BIDAYUH DIALEK BEMAK - Winardi, Bernadus; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted driven by the desire to document and inventory words and phrases in terms of fishing activities in the Sungai Landak stream. Problems discussed in this research, namely the form of lingual units, lexical meanings, cultural meanings and inventory of the term by using computerized linguistics Wesay. This research uses three methods including observation method, skill method, and descriptive method. Result of research of term fishing activity in Sungai Landak on Bidayuh language of Bemak dialect, (1) lingual unit form, divided into single word, derivative and phrase; (2) lexical meaning based on the category of noun appliance, result and activity verb; (3) the cultural meaning of abstinence with 3 data, consisting of abstinence, arrogance, not to mention crocodiles and myths with 4 data consisting of myths of misfortune, mythological ghost of water, mythical bird of bice 'keto' as nature marker; (4) an inventory by computerized linguistic Wesay, which produces a mini-dictionary related to fisheries. Keywords: Terminology, Fishing, Sense, Wesay